Assessment of Water Recycling Effectiveness for a Super-Intensive White Leg Shrimp Farm in Ca Mau Province - Nguyen, Thi Thu Thao (Journal of Technical Education Science, 2023)
Recycling shrimp farming water is a way to address the trend toward a circular economy in Vietnam's coastal regions while also reducing the quantity of effluent that is released into the environment. In order to explore the potential for waste recycling, this study investigates the pond system of a highly intense Littopenaeus vannamei culture area in Ca Mau province. The water balance approach was used to assess how effectively shrimp farms use water. In order to determine how much water helps to the financial success of shrimp farming, the value of water was also evaluated. According to the results of the water balance calculation, the current system could result in water losses of up to 1000 m3, accounting for over 20% the total water use. Only 33 m3 of water loss was estimated for the proposed water recirculation system, which was 3% of the current system. By recirculating the treated water back into the shrimp ponds, the farm also saved 20% of the water utilized for those ponds. The economic value of water was 6000 VND/m3 for the current farming system. The water value in the system would be decreased by 20% for the suggested treatment system. The high cost of investing in water recirculating technologies is related to the high water exchange rate. When deciding how much water to allocate, it should be taken into account.